2008
DOI: 10.1016/j.antiviral.2007.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Is the anti-psychotic, 10-(3-(dimethylamino)propyl)phenothiazine (promazine), a potential drug with which to treat SARS infections?

Abstract: Phenothiazine and derivatives were tested for inhibition of SARS-CoV replication. Phenothiazine slightly inhibited SARS-CoV replication in a neutral red (NR) uptake assay. Adding a propylamino group to give promazine reduced virus yields (VYR assay) with an EC(90)=8.3+/-2.8 microM, but without selectivity. Various substitutions in the basic phenothiazine structure did not promote efficacy. Phenazine ethosulfate was the most potent compound by VYR assay (EC(90)=6.1+/-4.3 microM). All compounds were toxic (IC(50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…In vitro data confirmed recent findings by Barnard et al (Barnard et al, 2008; Barnard et al, 2006b) that promazine, an antipsychotic drug, and ribavirin, a nucleoside analog, were not effective against SARS-CoV in vitro. Findings with v2163 supported prior findings that Infergen™ was active in vitro against SARS-CoV Urbani (Kumaki et al, 2008).…”
Section: Discussionsupporting
confidence: 88%
“…In vitro data confirmed recent findings by Barnard et al (Barnard et al, 2008; Barnard et al, 2006b) that promazine, an antipsychotic drug, and ribavirin, a nucleoside analog, were not effective against SARS-CoV in vitro. Findings with v2163 supported prior findings that Infergen™ was active in vitro against SARS-CoV Urbani (Kumaki et al, 2008).…”
Section: Discussionsupporting
confidence: 88%
“…Although, several reports delineated the efficacy of certain NSMIs viz., ribavirin, promazine , and IMP dehydrogenase inhibitors to inhibit in vivo models of SARS- CoV replication, later, they were proven ineffective ( 60 , 150 152 ). A report by Reghunathan et al ( 153 ) showed that the immune response produced against SARS-CoV may be different from other viral infections as indicated by the lack of upregulation in MHC-I genes, cytokines, and IFNs or complement-mediated cytolysis in peripheral blood mononuclear cells (PBMCs).…”
Section: Introductionmentioning
confidence: 99%
“…A total of six studies were included in scoping review and meta-analysis [19][20][21][22][23][24]. All studies originated from the United States of America (USA) and utilized mice and marmosets, but only the analyses with mice are taken into consideration.…”
Section: Characteristics Features Of the Included Studiesmentioning
confidence: 99%
“…The coronavirus disease that originated in 2019 (also referred to as COVID- 19) is an emerging infectious disease that is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The global pandemic disease which sprung forth from Wuhan City, in Hubei Province of China was rst reported by the World Health Organization (WHO) on 31 December 2019.…”
Section: Introductionmentioning
confidence: 99%